Sexual identity-related inequalities in associations between adverse childhood experiences and health in late adolescence-A national cohort study. - Rahul Chandrasekar; Alexis Karamanos; Annastazia Learoyd; Amal R Khanolkar (PLoS ONE)
This study examined associations between adverse childhood experiences (ACEs) and mental health and health-risk behaviours, including differences by sexual minority (SM) identity. We included 8,686 adolescents (males = 50.7%, SM = 10.3%) from the UK-wide Millennium Cohort Study with data on eight ACEs (e.g., domestic violence, parental psychological distress, bullying) recorded between ages 3-14 and a wide-range of health indicators and health-risk behaviours at age 17. Associations between 1) Sexual identity and ACEs were analysed using multinomial logistic regression and 2) Cumulative ACE scores and all outcomes were analysed using linear/logistic regression (with appropriate interactions assessing differences in ACE-outcome associations by sexual identity and adjusted for sex, ethnicity, and parental income). Results showed SM individuals had a higher prevalence of bullying (33.9% vs. 20.3%) and experiencing ≥3ACEs [Bisexual: RRR 1.87 (95% CI 1.35, 2.57), Gay/Lesbian RRR 2.08 (1.24, 3.48)]. The number of individuals experiencing adverse mental health outcomes increased in relation to greater ACE exposure with evidence for effect-moderation by sexual identity in certain outcomes. For example, among individuals with 0 ACEs, 8% of heterosexual adolescents reported psychological distress vs. 22% in bisexual and 17% in gay/lesbian peers, increasing to 16% in heterosexual vs. 41% in bisexual and 45% in gay/lesbian adolescents with ≥3 ACEs. Similar patterns were observed for other health indicators (e.g., self-harm, suicidality, sleep quality) and health-risk behaviours (e.g., risky sex). Our findings indicate that ACEs are associated (with a gradient) with worse mental health and well-being, and higher risk of some health-risk behaviours. However, the detrimental effect of ACEs on health is worse in SM adolescents compared to heterosexual peers.